Physical chemistry of gas-liquid interfaces - Faust, Jennifer A.; House, J. E. (Developments in physical & theoretical chemistry., 2018)
Physical Chemistry of Gas-Liquid Interfaces, the first volume in the Developments in Physical & Theoretical Chemistry series, addresses the physical chemistry of gas transport and reactions across liquid surfaces. Gas-liquid interfaces are all around us, especially within atmospheric systems such as sea spry aerosols, cloud droplets, and the surface of the ocean. Because the reaction environment at liquid surfaces is completely unlike bulk gas or bulk liquid, chemists must readjust their conceptual framework when entering this field. This book provides the necessary background in thermodynamics and computational and experimental techniques for scientists to obtain a thorough understanding of the physical chemistry of liquid surfaces in complex, real-world environments.